SALE AND PURCHASE FINANCING AND PROFIT SHARING ON NON-PERFORMING FINANCING AND ITS IMPLICATIONS FOR THE FINANCIAL PERFORMANCE OF SHARIA PEOPLE'S CREDIT BANKS - Yusriyyah Yusriyyah; Umiyati Umiyati (Faculty of Economic and Social Science, Universitas Islam Negeri Sultan Syarif Kasim, 2024)
This study aims to examine the direct and indirect effects of Sale-Purchase Financing and Profit-Sharing on Non-Performing Financing and their implications for the financing performance of Bank Perkreditan Rakyat Syariah (BPRS) during the period 1st quarter 2017 – 4th quarter 2021. Samples were taken using the Non Probability Sampling with purposive sampling method. The samples used in this study were 4 BPRS representing the sampling criteria determined by the author. The data that has been obtained is processed through the path analysis method with the analysis tool Eviews 12 and Microsoft Excel. The results of this study indicate that there is a direct effect between Profit-Sharing Financing ( ) on Non Performing Financing (Z), Sale-Purchase Financing ( ) on Return On Assets (ROA) (Y), and Non Performing Financing (Z) on Return On Assets (ROA) (Y). Meanwhile, profit sharing financing ( ) has an indirect effect on Return On Assets (ROA) (Y) through Non Performing Financing (Z).